The use of anglicisms among teenagers - Padilla Piedra, María Elizabeth; Sánchez Espinoza, Christian Santiago
Anglicisms are a part of Neologisms. The word Neologism means a term, phrase, or idiom which is borrowed from another language. In the Spanish language, Anglicisms have been influenced adding new terminologies, connotations, and replacing other terms. Teenagers are more involved in speaking Anglicisms due to different reasons, such as immigration of Ecuadorians to English speaking countries, influence of TV, music, and internet. In addition, the youth often attempt to add style to their language by changing some words and their true meaning or simply transforming them as verbs, nouns, or adjectives. On the other hand, Anglicisms are sometimes used as initials without taking into consideration its meanings, but their idea. Probably the same problem native speakers share with us. There is not just one single field to speak Anglicisms, but many others. We found out 12 categories of Anglicisms that are common among teenagers when speaking. They are related to clothing, sports, technology, business, family, home, entertainment, school, music, food, fashion, and informal language. In addition, we analyzed and exemplified the syntax, morphology, and connotation of them.